The application of resveratrol to mesenchymal stromal cell-based regenerative medicine - Chenxia Hu; Lanjuan Li (Stem Cell Research & Therapy, 2019)
Abstract Currently, the transplantation of mesenchymal stromal cells (MSCs) has emerged as an effective strategy to protect against tissue and organ injury. MSC transplantation also serves as a promising therapy for regenerative medicine, while poor engraftment and limited survival rates are major obstacles for its clinical application. Although multiple studies have focused on investigating chemicals to improve MSC stemness and differentiation in vitro and in vivo, there is still a shortage of effective and safe agents for MSC-based regenerative medicine. Resveratrol (RSV), a nonflavonoid polyphenol phytoalexin with a stilbene structure, was first identified in the root extract of white hellebore and is also found in the roots of Polygonum cuspidatum, and it is widely used in traditional Chinese medicine. RSV is a natural agent that possesses great therapeutic potential for protecting against acute or chronic injury in multiple tissues as a result of its antioxidative, anti-inflammatory, and anti-cancer properties. According to its demonstrated properties, RSV may improve the therapeutic effects of MSCs via enhancing their survival, self-renewal, lineage commitment, and anti-aging effects. In this review, we concluded that RSV significantly improved the preventive and therapeutic effects of MSCs against multiple diseases. We also described the underlying mechanisms of the effects of RSV on the survival, self-renewal, and lineage commitment of MSCs in vitro and in vivo. Upon further clarification of the potential mechanisms of the effects of RSV on MSC-based therapy, MSCs may be able to be more widely used in regenerative medicine to promote recovery from tissue injury.